2017
DOI: 10.3389/fpls.2017.01346
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Regulates Potential Genes Involved in Major Physiological Processes in Plants to Combat Stress

Abstract: Silicon (Si), the quasi-essential element occurs as the second most abundant element in the earth's crust. Biological importance of Si in plant kingdom has become inevitable particularly under stressed environment. In general, plants are classified as high, medium, and low silicon accumulators based on the ability of roots to absorb Si. The uptake of Si directly influence the positive effects attributed to the plant but Si supplementation proves to mitigate stress and recover plant growth even in low accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(77 citation statements)
references
References 110 publications
1
67
0
1
Order By: Relevance
“…According to the results of Debona et al (2017), Si regulates stress from metal toxicity by modulating the pH range of soil or changing metal speciation while Xiao et al (2014) suggested metal co-precipitation and the formation of inorganic crystals (facilitated by Si) in carbonaceous materials like biochar as a mechanism to abate metal toxicity. Recently, Manivannan and Ahn (2017) suggested the involvement of Si in regulating genes that affect photosynthesis during metal toxicity and the modulation of the expression of housekeeping genes during disease infection. Genes involved in water uptake and transportation and those involved in the expression of defense response in plants are also modulated by Si (Manivannan and Ahn, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results of Debona et al (2017), Si regulates stress from metal toxicity by modulating the pH range of soil or changing metal speciation while Xiao et al (2014) suggested metal co-precipitation and the formation of inorganic crystals (facilitated by Si) in carbonaceous materials like biochar as a mechanism to abate metal toxicity. Recently, Manivannan and Ahn (2017) suggested the involvement of Si in regulating genes that affect photosynthesis during metal toxicity and the modulation of the expression of housekeeping genes during disease infection. Genes involved in water uptake and transportation and those involved in the expression of defense response in plants are also modulated by Si (Manivannan and Ahn, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Manivannan and Ahn (2017) suggested the involvement of Si in regulating genes that affect photosynthesis during metal toxicity and the modulation of the expression of housekeeping genes during disease infection. Genes involved in water uptake and transportation and those involved in the expression of defense response in plants are also modulated by Si (Manivannan and Ahn, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Si accumulation also affects the plant structure, increasing the tissue structure firmness, reducing lodging and plant breaking, besides contributing to a greater crop yield (Epstein 1999, Korndörfer & Lepsch 2001, Hattori et al 2005, Ahmed et al 2014, Manivannan & Ahn 2017. A reduction in the percentage of lodged sorghum plants was observed in the soil fertilized with Si.…”
Section: Genotypesmentioning
confidence: 99%
“…Silicon accumulation is associated with plant structural features that increase the structural rigidity of tissues and reduce lodging. In addition, Si promotes the formation of more upright leaves, decreasing self-shading, increasing the leaf area (and consequently the photosynthesis efficacy) and plant growth, as well as leading to a higher crop yield (Epstein 1999, Korndörfer & Lepsch 2001, Hattori et al 2005, Ahmed et al 2014, Manivannan & Ahn 2017.…”
Section: Introductionmentioning
confidence: 99%
“…A previously conducted experiment shows that Si can decrease OH hydroxyl radical accumulation in cucumber leaves by reducing the free apoplastic Mn +2 [ 19 ]. One of the other protective roles of silicon is regulating internal water in plants [ 22 ] so that the accumulation of silicon in epidermal tissue preserves water in the transpiration process [ 23 ]. Generally, plants tend to accumulate heavy metals, such as cadmium, in the root more than shoot and stem [ 24 ].…”
Section: Introductionmentioning
confidence: 99%